2004
DOI: 10.1002/tox.20044
|View full text |Cite
|
Sign up to set email alerts
|

Field study on changes in viability of airborne fungal propagules exposed to UV radiation

Abstract: The responses of airborne fungi to UV-B under natural conditions were investigated at the coastal station in Preila, Lithuania. Results of this investigation demonstrated that solar radiation has a marked lethal effect on outdoor airborne fungi. Sensitivity to solar radiation was the highest for the fungal propagules collected late in the evening (relative recovery 6.2%) and early morning (25.3%). The lowest sensitivity to solar radiation was observed for fungal propagules collected at midday (50.0%) and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
(20 reference statements)
2
19
0
1
Order By: Relevance
“…These results are similar to those reported for potato late blight, where solar radiation is the most important variable in survival of Phytophthora infestans sporangia (64). Deleterious effects of solar radiation on spores are primarily due to the UV-B spectrum (112). Total solar radiation has been found to explain the same degree of variation in survival of P. cubensis sporangia as does UV radiation (54).…”
Section: Survival Of Pseudoperonospora Cubensis Sporangiasupporting
confidence: 77%
“…These results are similar to those reported for potato late blight, where solar radiation is the most important variable in survival of Phytophthora infestans sporangia (64). Deleterious effects of solar radiation on spores are primarily due to the UV-B spectrum (112). Total solar radiation has been found to explain the same degree of variation in survival of P. cubensis sporangia as does UV radiation (54).…”
Section: Survival Of Pseudoperonospora Cubensis Sporangiasupporting
confidence: 77%
“…Some authors have suggested that conidia pigmentation could represent an important protection against UV radiation . Three differently coloured conidia of Aspergillus were tested in our experiment: yellow, green and black, belonging to sections Circumdati , Flavi and Nigri , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although information concerning the effects of UV‐B on fungi and bacteria is scarce, studies on microfungal communities in soils of extreme habitats, such as desert (very high solar radiation, drought, and extreme temperatures), suggest the dominance of dark‐coloured microfungi with large multicelled conidia . Likewise, the main airborne fungal species identified at a coastal station after exposure to solar radiation were predominantly Aspergillus niger , Alternaria alternata , Cladosporium cladosporoides and Arthrinium phaerosporum . Therefore, Aspergillus species could prevail over other species under high‐UV‐radiation environments.…”
Section: Introductionmentioning
confidence: 99%
“…Some bacteria (e.g., QT4, QT6) presented in the enhanced UV-B treatment, not in CK. This may because species diversity was affected by solar UV-B radiation because of species-specific sensitivity to the radiation and another studies reported that UV-B radiation could alter the plant and its root exudates, so some of the soil bacteria were stimulated or inhibited (Kashimada et al 1996;Piccini et al 2009;Ulevičius et al 2004). …”
Section: Discussionmentioning
confidence: 96%